Vital Signs Monitoring Device with BPM and SpO2 Notification to the Internet of Things Based on Telegram App - Luthfiyah, Sari; Ramadhani, Elga Rahmah; Indrato, Tri Bowo; Wongjan, Anan (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Vital signs are an important component of monitoring the adult or child patient’s progress during hospitalization, as they allow for the prompt detection of delayed recovery or adverse events. Vital signs are measured to obtain basic indicators of a patient’s health status. The most common intervention performed in hospital medicine is a measurement of vital signs and these traditionally consist of blood pressure, temperature, pulse rate, and respiratory rate. Advanced monitoring systems incorporate a balanced combination of clinical and technological aspects to give an innovative healthcare outcome. Remote patient monitoring systems are rapidly becoming the core of healthcare deliveries. The paradigm shifted from traditional and manual recording to computer-based electronic records and further to smartphones as versatile and innovative healthcare monitoring systems. The purpose of this research is to design a Vital Sign Monitoring device for BPM and SpO2 Parameters with Notifications through the IoT-Based Telegram application. This device can monitor vital signs, especially BPM and SPO2 wherever the patient is and whenever, so that doctors or health workers, as well as patients, can find out their health condition. This display can be viewed via web thinger.io, then forwarded to telegram if an abnormal patient condition is found and there is an indicator light that will light up differently for each condition. This study uses the MAX30100 which is a digital sensor to detect oxygen saturation and heart rate. The results of this study have succeeded in displaying data on the IoT web and sending notifications to the Telegram application. And also, the resulting data has an error that does not exceed the allowable limit according to each parameter. The difference between heart rate readings and oxygen saturation values ​​on the device and patient monitor is 0.015% for heart rate and 0.01% for oxygen saturation.